Alkaloids Lead to Potential Inhibition of the Acyl Carrier Protein Reductase to Attenuate Tuberculosis; an in-silico Analysis - Kamran, Pernia; Ibrahim, Ahsan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Tuberculosis (TB) is a contagious infection that mostly affects the lungs. Mycobacterium tuberculosis causes tuberculosis infection, leading to granulomatous lesions in affected lung tissue. It is one of the most prevalent and deadly infectious diseases among the under developed countries. This study aims to investigate the possible inhibition of the acyl carrier protein reductase for preventing tuberculosis by well-known alkaloids, thereby reducing Mycobacterium tuberculosis growth in the lungs and thereby reducing the incidence of latent and active TB. About five natural alkaloids were subjected to the molecular docking analysis, which produced favorable findings in terms of best pose and binding energies of these compounds towards the active residues of mycobacterial ACP reductase, with values ranging from -10 kcal/mol to -9.1 kcal/mol. The molecular dynamics simulation produced similar encouraging results. All of the prospective alkaloid compounds were subjected to an in-silico toxicity investigation, which determined that every compound was safe and non-toxic. Further studies may be necessary for effective formulation development employing these compounds as part of the process of drug discovery and development. The findings from this study may be helpful in the development of the novel nanoformulations using natural products for pharmacotherapy of tuberculosis infection.